Evaluation of a simple colorimetric analysis for urinary malondialdehyde determination - A Suha Yalçın; Ahmet Kılınç Burak Cöbek (Dove Medical Press, 2010)
A Suha Yalçın1,2, Ahmet Kılınç2, Burak Cöbek21Department of Biochemistry, School of Medicine, Marmara University, Haydarpaşa-I˙Stanbul Turkey; 2Oksante R&D Laboratory, GOSB Teknopark, Gebze-Kocaeli, TurkeyAbstract: Oxidative stress results when the amount of free radical formation exceeds the capacity of the antioxidant defense system. It is related to a number of pathological conditions including: cardiovascular disease, neurodegenerative disease, cancer, diabetes mellitus, gastrointestinal system disorders, inflammation and aging. It is difficult to quantify free radicals directly due to their reactive nature and short half-life. For this reason, most people prefer to measure antioxidant levels and/or the end products of free radical attack on macromolecules such as lipids, proteins and nucleic acids. In this study we have established a short and easy method to determine urinary levels of malondialdehyde, an end product of lipid peroxidation. The method depends on the spectroscopic measurement of color intensity of the product formed by the reaction of the aldehyde groups with the Schiff reagent. The method is linear at a concentration range of 1–10 µM and correlates with the widely used thiobarbituric acid method.Keywords: urinary malondialdehyde, oxidative stress, Schiff reagent